174k views
2 votes
Heidi solved the equation 3(x + 4) + 2 = 2 + 5(x – 4). Her steps are below: 3x + 12 + 2 = 2 + 5x – 20 3x + 14 = 5x – 18 14 = 2x – 18 32 = 2x 16 = x Use the drops-downs to justify how Heidi arrived at each step. Step 1: Step 2: Step 3: Step 4: Step 5:

User JayG
by
5.1k points

1 Answer

2 votes

Answer:

see below

Explanation:

3(x + 4) + 2 = 2 + 5(x – 4)

Distribute using the distributive property

3x + 12 + 2 = 2 + 5x – 20

Combine like terms (simplify)

3x + 14 = 5x – 18

Subtract 3x from each side using the subtraction property of equality

14 = 2x – 18

Add 18 to each side using the addition property of equality

32 = 2x

Divide each side by 2 using the division property of equality

16 = x

User AscendingEagle
by
5.9k points